Material Requirements Planning System for Mcdonald’s Branch PTT Ayutthaya - งามขำ กนกอร; จิระวิชิตชัย นิเวศ (Progress in Applied Science and Technology, 2017)
The objectives of this research are to develop material requirements planning system in the mcdonald ’s branch PTT ayutthaya. This system was developed to support the decision of the manager branch about product list, suppliers, ending stock and order requirements planning. The system developed allows the manager branch to quickly and easily manage and reduce the complexity of managing documents as well. Evaluation of results from tests performed by manager branch was found to be an effective system. It was developed at a good level and can be used effectively.